KEMAMPUAN MENGAJAR GURU DITINJAU DARI LATAR BELAKANG PENDIDIKANNNYA - Mutia Novarina; Nova Sari (STKIP An-Nur, 2021)
This research is a case study research with a qualitative approach this research is entitled “Teaching Ability of Teacher reviewed from Their Educational Background”. This is based on Ministerial Regulation 137 article 29 paragraphs 4, which states that educators in Early Childhood Education must have a minimum educational academic qualification of Diploma IV or bachelor's degree. The teacher who teaches at TKIT Baitusshalihin has different levels and educational qualifications. Therefore, this study aims to determine the teaching ability of teachers in terms of educational background at TKIT Baitusshalihin, Ulee Kareng District. The number of respondents in this study was TKIT Baitusshalihin teachers total of 10 teachers who had an undergraduate education background of 6 teachers, DII amounted to 1 teacher, and SMA totaled of 3 teachers. Data collection was carried out using interviews, observation, and documentation methods. The study found differences in the implementation of teaching and learning activities for teachers from the planning and implementation aspects, but there were no differences in the aspects of assessment among teachers who had S1, DII, and SMA educational backgrounds in TKIT Baitusshalihin, Ulee Kareng District. Keywords: teaching ability, teacher, educational background